Effect of sintering condition on electrical properties of PLZT ceramics - Narit Funsueb (2018)
© 2016 Trans Tech Publications, Switzerland. Ferroelectric lead lanthanum zirconate titanate (PLZT) ceramics 9/70/30 were synthesized by conventional mixed-oxide method via a vibro-milling technique. The effect of sintering temperature and two-stage sintering method on electrical properties of PLZT ceramics was investigated. The ceramic powder was uniaxially pressed in pellets and sintered at the temperatures ranging from 1200 to 1275 °C for 4hrs and two-stage sintering temperature at 1200 °C for 4 hrs. Dielectric, ferroelectric and strain properties of ceramics were characterized by LCR meter, modified Sawyer-Tower Circuit and modified Michelson interferometric technique respectively.